Analysis of Finished Product Warehouse Activity Flow Using Lean Warehouse Method - Naia Putri Harendsa; Farida Pulansari (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2025)
This company is a light steel processing manufacturing company that specializes in the production of hollow structural sections. A warehouse is the main component that enables a company's operational functions. The role of the warehouse is not only focused on storage and distribution but also on operational efficiency which can have an impact on business competitiveness. Warehousing activities at this company ain’t been optimal due to waste. Waste that occurs such as searching for empty areas for storage, waiting time for the next process, repeated product inspections, has an impact on the flow of warehousing activities. This study seeks to assess the amount of waste and provide recommendations to minimize waste within the finished product warehousing operations at this company. This study uses the Lean Warehousing method consisting of Value Stream Mapping, Process Activity Mapping, and 5 Whys Analysis. The results of this study identify 4 wasteful activities with the highest time such as waiting for the customer’s cargo truck to pick up products (I10), moving products to the truck loading bed (C5), moving products from the production floor to the storage area (S5), waiting for the next process in order to move products (P2). The proposed improvements can reduce 8 non-value-added activities and trim activity time by 1015 minutes. The suggested improvements also increase Process Cycle Efficiency by 15.32% from 11.17% to 26.49%. This proves that the implementation of lean warehouse can improve efficiency and service quality as a whole.